96.9k views
11 votes
Rewrite the product using the Distributive Property. Then simplify.

1) 2(4 + 7)
2) 3(1/3 - p)

1 Answer

9 votes

Answer:


2(4 + 7) = 22


3((1)/(3) - p) = 1 - 3 p

Explanation:

Given

1 & 2

Required

Rewrite and simplify


1.\ 2(4 + 7)

Apply distributive property


2(4 + 7) = 2 * 4 + 2 * 7


2(4 + 7) = 8 + 14


2(4 + 7) = 22


2.\ 3((1)/(3) - p)

Apply distributive property


3((1)/(3) - p) = 3*(1)/(3) - 3 * p


3((1)/(3) - p) = (3)/(3) - 3 * p


3((1)/(3) - p) = 1 - 3 * p


3((1)/(3) - p) = 1 - 3 p

User Seho
by
5.0k points